SINKRONISASI CHAOS SIRKUIT LORENZ SERTA APLIKASINYA DALAM SISTEM KEAMANAN KOMUNIKASI - Mada Sanjaya WS; Siti Nurlaela (JURNAL ISTEK, 2011)
Lorenz circuit is an autonomos three-dimensional system and a simple nonlinear circuits that can generate chaotic dynamics including the presence of variations in phase diagrams and attractors. In this paper, has been built the circuit design and numerical simulation based on the basic circuit Lorenz. The result of numerical simulations and electronic circuits are used to show the accuracy of the theoretical design and implementation of the circuit are made. Matlab program and Multisim is used to simulate the numerical implementation of the Lorenz circuit and shows the presence of chaos. In this paper, we have developed an application of chaotic signal as a signal modulator that can be used for secure communication systems.